Comparative analysis of the General State Budget and its influence on fiscal policy in Ecuador, period 2019-2020 - Moyón Sánchez, Luis Andrés (2020)
Objective: Carry out a comparative analysis of the General State Budget and its influence on improving the quality of life of Ecuadorians based on public spending. Method: The type of research was descriptive because it allowed observation to determine the characteristics of the variables studied and applied, since the knowledge was used to carry out a quantitative and percentage comparative analysis between the income and expenditure groups of the General State Budgets. Results: The results show that applying a restrictive monetary policy has caused an increase in unemployment, less coverage of social services and poverty. Conclusions: Optimizing public spending is possible, but the path of austerity cannot be the only way to reduce the wage bill.